Medical pluralism in maternal health-seeking behavior of rural women in Southern Ecuador. Issue 4 (1st July 2021) - Arnold, Jessica; Flint, Julia; Casapulla, Sharon; Nieto, Claudia; Grijalva, Mario J.
Abstract: In rural Ecuador pregnant women face complex challenges navigating the terrain between traditional and biomedical maternal health care services. Semi-structured interviews were conducted in three rural communities in Southern Ecuador that have presented active Chagas disease transmission with women who were pregnant or have given birth within the last five years. This study was conducted to identify and understand the experiences of mothers in these communities and the decisions they make to maintain the wellness of themselves and their children. The researchers recorded women's maternal health stories, analyzed their access to maternal health care, and explored factors influencing their birth location preferences and health seeking behaviors. The researchers found that women in this region are utilizing medical pluralism to sustain maternal health and the well-being of their children.